The Validity of Settlement Agreements That Override Final and Binding Court Decisions According to Article 1320 of the Civil Code - Bryan Eunico (Judge : Jurnal Hukum, 2025)
Legal disputes between legal entities in the realm of civil law can be resolved through litigation in a district court or through non-litigation outside of court based on an amicable agreement between the parties. This study aims to discuss the legal issue of the validity of a settlement agreement made by the disputing parties, whereby the contents of the settlement agreement override a court decision that has permanent legal force, based on the interpretation of Article 1320 of the Civil Code regarding the validity requirements of an agreement. In researching this issue, a normative legal research method was used. The results of the study conclude that a settlement agreement that overrides a final and binding court decision by the parties who agree to it, when viewed based on the provisions of Article 1320 concerning the validity of agreements, does not conflict with the validity of agreements and can be interpreted as a breakthrough in the settlement of disputes arising from judicial proceedings. A settlement agreement that has executory power and can be requested for execution is a settlement agreement agreed upon by the parties before the case is decided at the first level of legal proceedings, confirmed by a Settlement Agreement by the panel of judges, and if agreed upon after the court decision at the first level of legal proceedings, submitted in writing to the Examining Judge at the appeal level, appeal, or review to be decided by a Settlement Deed.